(untitled) (Research, Society and Development, 2021)
A new highly contagious virus emerged in December 2019 in China and cases quickly began to spread around the world, causing fear in all nations. The disease called “coronavirus disease 2019” (COVID-19) has become the most serious public health problem of this generation. In the pediatric age group, the clinical manifestations of COVID-19 can involve any device and system, from asymptomatic conditions to death. The aim of this study was to describe the experience of a pediatrician in child health care while facing the COVID-19 pandemic. This is an experience report about his experience during the pandemic, built through the author’s own narratives based on his memories, from the first cases to the arrival of the virus in his daily life. One of the main problems faced was the lack of personal protective equipment. Appropriate protective measures for all professionals, in addition to psychological support, must be implemented in health services, in order to minimize the emotional burden.